Providing care for young adults with type 2 diabetes in primary care settings in Singapore: a multi-faceted study - Wong, Sabrina Kay Wye (Nanyang Technological University, 2022)
In this doctorate dissertation, a population-, practice- and patient-based approach was used to assess care in young-onset diabetes. Studies were conducted using four different methodologies. The first, a longitudinal database study, examined clinical outcomes in young-onset diabetes. The second study, a systematic review, evaluated the effectiveness of prior self-care interventions. The third study, a cross-sectional survey, examined self-care behaviours and the impact of psychological health and self-efficacy using network analysis. The fourth, a qualitative study utilising in-depth interviews, identified barriers and facilitators of self-care behaviours. Results showed poor metabolic profiles in young-onset diabetes and a lack of effectiveness of prior self-care interventions. Network analysis suggested that self-efficacy and psychological health had a central or direct roles in diet and exercise behaviours. A mindset- based approach was identified qualitatively that could inform the design of an individualised care intervention.